Evaluation of Nutritional Content of Quail Eggs Bacem, Pindang, and Balado in Retort Pouch for Stunting Prevention - Puspasari, Diah Ayu; Hartiningsih, Subekti; Mariani, Elisa (Fakultas Pertanian Universitas Veteran Bangun Nusantara, 2025)
Stunting remains a major chronic nutritional problem in Indonesia, especially among children in areas with limited food access. One of the main causes is the lack of high-quality animal protein intake. Quail eggs are a potential source of protein, fat, vitamins, and minerals, but are highly perishable and require processing and packaging innovations to extend shelf life and maintain nutritional quality. This study aimed to evaluate the moisture, protein, and fat content of bacem, pindang, and balado quail eggs in